LITERATURE REVIEW AND THEORETICAL FRAMEWORK OF UTILIZING PROVERBS AND SAYINGS IN LANGUAGE TEACHING - Nilufar Jamoliddinova; Jasmina Davranova (American Journals Publishing, 2025)
The article explores the significance of proverbs and sayings in language teaching, emphasizing their cultural and educational value. It highlights the role of these concise expressions in vocabulary acquisition, cultural immersion, critical thinking, and memory retention. Drawing from their roots in oral folklore, the article discusses the historical and cultural context of proverbs and sayings, underscoring their ability to convey collective wisdom, social norms, and traditions. Practical strategies for integrating these expressions into educational settings are also examined, showcasing their potential to enhance linguistic and cultural competence among learners.
Keywords: Proverbs, sayings, language teaching, cultural immersion, vocabulary acquisition, oral folklore, linguistic competence, cultural literacy, memory retention, educational strategies.